Analysis of the Correlation Between Serum Vitamin D Levels and Severity of Atopic Dermatitis - Mariz,Juliana Câmara (2021)
ABSTRACT Introduction: Atopic dermatitis (AD) is a chronic inflammatory multifactorial disease. Severe cases affect the quality of life. The pathogenesis is complex, marked by defective cellular immune system, exacerbation of Th2-type immune response and impaired skin barrier function. Studies suggest that vitamin D acts in the regulation of the innate and adaptive immune response, reduces the inflammatory process and improves the skin barrier. Our objective was to correlate vitamin D serum levels with the severity of AD. Material and Methods: Between 2015 and 2018 the authors evaluated 30 patients aged between 18 and 90 years old, under treatment at a Dermatology ambulatory clinic. Patients were divided into 2 groups: mild disease (only topical therapy) and moderate to severe disease (under immunosuppressive treatment). Results: Ten cases with mild AD and 20 with moderate to severe AD were selected. Among patients with mild disease, 20% had vitamin D deficiency. As for patients with moderate to severe disease, 40% had a deficient serum level of 25-hydroxyvitamin D. Comparing the average vitamin D in the two groups, there was no statistical difference between them. Conclusion: In the literature, the association between vitamin D levels and the severity of AD remain controversial, although some studies support this association. In this study, despite the proportion of patients with 25-hydroxyvitamin D deficiency being twice as high among patients with moderate to severe AD, there was no statistical significance between the groups, corroborating previous manuscripts. Clinical studies relating atopic dermatitis to vitamin D are warranted, considering its possible use as a concomitant therapy.